Mechanism design without quasilinearity - Tomoya Kazumura; Debasis Mishra; Shigehiro Serizawa (Osaka University, Institute of Social and Economic Research (ISER), 2017)
This paper studies a model of mechanism design with transfers where agents' preferences need not be quasilinear. In such a model, (1) we characterize dominant strategy incentive compatible mechanisms using a monotonicity property; (2) we establish a revenue uniqueness result: for every dominant strategy implementable allocation rule, there is a unique payment rule that can implement it; and (3) we show that every dominant strategy incentive compatible, individually rational, and revenue-maximizing mechanism must charge zero transfer for the worst alternative (outside option). These results are applicable in a wide variety of problems (single object auction, multiple object auction, public good provision etc.) under suitable richness of type space. In particular, our results can be applied to models where preferences of agents are arbitrarily small perturbations of quasilinear preferences and illustrate the (non)-robustness of some of the classic results in mechanism design with quasilinearity. We show various applications of our results.
Keywords: D82; D44; D40; 330; incentive compatibility; individual rationality; monotonicity; non-quasilinear preferences; revenue equivalence